Karnoprawna ochrona nekropolii - Daszkiewicz, Wiesław (Wydział Prawa i Administracji UAM, 1989)
Cult of the dead, their various last resting-places and ceremonies connected with burials or cremations should be protected by law. There is a clear link between those elements and a spiritual sphere of a human being and his/her personal (immaterial) interests. Such interests, as well as various related material interests are protected i.e. by penal law. Several legal acts should be mentioned here, in particular the Penal Code of 1969, the Petty Offences Code of 1971, the Act on Cemeteries and Burials of 1959 and the Act on Military Cemeteries of 1933. The objects located on cemeteries or even the whole cemeteries are monuments and thus they are also subject to protection provided for in the Act on Protection of Cultural Values and on Museums of 1962. Generally speaking, penal law norms on protection of cemeteries could be divided into 4 groups. The first contains norms determining offences and petty offences against the cult of the dead, against their last resting-places, and against the freedom to engage in funeral ceremonies. The second group contains provisions penalizing the violation of norms regulating the exploitation of cemeteries (including sanitary regulations, exhumation permits, transportation of corpses, etc.). To the third group belong the provisions on responsibility for offences and petty offences against property, (including the provision on protection of objects having no material value). Finally, the fourth group is composed of norms protecting monuments as values of culture. The article presents penal law instruments contained in the above 4 groups, sketches the evolution those measures have undergone in Polish law, and puts forth de lege ferenda postulates. The Penal Code of 1969 instead of two offences provided in a former code of 1932, one of which consisted in profaning the corpse or maliciously disturbing a funeral ceremony, the other in taking a corpse or its part away from the entitled person's possession — introduced one offence in two forms (Art. 197), A basic form, with a penalty of imprisonment of up to 3 years, consists in maliciously disturbing a funeral ceremony or in profaning the corpse, ashes, or the last resting-place of the dead, whereas a qualified form of that offence, with a penalty of 1-10 years of imprisonment has an additional feature: plundering the corpse, the grave or any other last resting-place of the dead. Both forms of the analysed offence require intention (dolus directus) and a definite motive of action. The subject-matter of protection provided for in Art. 197 is the freedom of conscience and religion in the sphere of the cult of the dead. Let me add that Art. 197 grants protection to funeral ceremonies and last resting-places irrespective of their secular or sacral character. Paragraph 2 of Art. 197 may be a source of difficulties. Namely, it is sometimes understood as prohibiting willful taking of property from the corpse, the grave or from another resting-place. Thus "plundering" is considered to be tantamount to an ordinary theft commited at the last resting-place of the dead, eg. stealing a tombstone without the intention of profaning the place.
Penal-law protection of necropolises